Exogenous spermidine alleviates oxidative damage and reduce yield loss in rice submerged at tillering stage - Liu, Ming; Chu, Meijie; Ding, Yanfeng; Wang, Shaohua; Liu, Zhenghui; Tang, She; Ding, Chengqiang; Li, Ganghua (Frontiers in Plant Science, 2015)
To figure out whether spermidine (Spd) can alleviate oxidative damage on rice (Oryza.sativa L.) caused by submergence stress, Ningjing 3 was used in this study. The results showed that, spraying Spd on rice leaves at a concentration of 0.5 mM promoted the growth recovery of rice after drainage, such as green leaves, tillers and aboveground dry mass. According to physiological analysis, Spd accelerate restored chlorophylls damage by submergence, and decreased the rate of O2-. generation and H2O2 content, inhibited submergence-induced lipid peroxidation. Spd also helped to maintain antioxidant enzyme activities after drainage, such as SOD, POD and GR, which ultimately improved the recovery ability of submerged rice. With the effect of Spd, the rice yields increased by 12.1%, 17.9%, 13.5% and 18.0%, of which submerged for 1, 3, 5, 7 days, respectively. It is supposed that exogenous Spd really has an alleviate effect on submergence damage and reduce yield loss of rice.